(untitled) (Research, Society and Development, 2019)
The purpose of this article is to present a didactic-pedagogical proposal, carried out in the Advanced Campus of Carmo de Minas, under the constructivist bias of Vygotsky. This experience consists in the fulfillment of the Integrator Project (interdisciplinary action) of the Pedagogical Project of the Course (PPC) of Integrated Informatics to High School. The discussion responds to the following research problem: is it possible to study and learn philosophy through the development of an electronic game using programming language? The analysis was done through a literature review and the response of a questionnaire applied to students with objective questions and a discursive one. Based on the theoretical reference, where authors make a defense of the use of the technologies in the formal educational environment, it is understood the plausibility of the realization of the Project in particular, by the implementation in the classroom of the Digital Technologies of Information and Communication (TDIC) Therefore, this research allows an open reflection to readers, teachers, students and researchers about the benefits, such as facilitators, that is, accessibility to technological means, and the challenges in making use of TDIC as mediation in teaching and learning.